2013
DOI: 10.1007/bf03353753
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Magnetic Properties of Monodisperse Fe3+-doped CeO2 Nanospheres

Abstract: Abstract:This work reports the study concerning the structure and magnetic properties of undoped CeO2 and Fe-doped CeO2 (Ce1−xFexO2, 0.01 ≤ x ≤ 0.07) nanospheres with diameters of 100∼200 nm prepared by hydrothermal method using polyvinylpyrrolidone (PVP) as surfactant. The prepared samples were studied by using X-ray diffraction (XRD), Raman spectroscopy, transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HRTEM), X-ray absorption near-edge structure (XANES), and vibratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…This indicates that O sublattice is affected as a result of change in grain size and doping. 35 However, the peak appears at around 670 cm À1 might be attributed to second-order Raman transition of CeO 2 . 36 Further, the intensity of intrinsic V O mode at about 620 cm À1 and second-order Raman transition about 670 cm À1 in CeO 2 lms suppresses for higher N ion uences (i.e., N 1E16 and N 6E16 ).…”
Section: Raman Spectroscopymentioning
confidence: 98%
“…This indicates that O sublattice is affected as a result of change in grain size and doping. 35 However, the peak appears at around 670 cm À1 might be attributed to second-order Raman transition of CeO 2 . 36 Further, the intensity of intrinsic V O mode at about 620 cm À1 and second-order Raman transition about 670 cm À1 in CeO 2 lms suppresses for higher N ion uences (i.e., N 1E16 and N 6E16 ).…”
Section: Raman Spectroscopymentioning
confidence: 98%
“…Several studies on Fe-doped CeO2 with a Fe content as high as 10 at.% reported a contraction of the CeO2 network induced by the introduction of (smaller) Fe 3+ ions at Ce 4+ sites[50,51] following a Vegard law model. On the contrary, Phokha and coworkers[52] observed an increase of the cell parameter of Fe-doped CeO2 with increasing the amount of hosted Fe, which was explained by the presence of Ce 3+ ions (larger than Ce4+ ions) in the lattice. The present Fe-doped CeO2 samples experience only tiny variations of unit cell parameter, a 0.002 % decrease being barely observed with Ce_Fe6 sample.…”
mentioning
confidence: 91%
“…Flytzani-Stephanopoulos et al [14] used different nanostructured CeO 2 materials as a support to deposit gold clusters and found that Au/CeO 2 catalysts showed a strong support shape effect in the water-gas shift reaction. Most of the properties of cerium oxide was found to be related with oxygen vacancies in the structure [1518]. …”
Section: Introductionmentioning
confidence: 99%